Income Tax and Top Incomes over the Twentieth Century. - Atkinson, A (2004)
The first section of the paper gives a stylised account of the development of the UK income tax structure over the past 200 years, and refers to recent changes in other OECD countries. The second section turns to the distribution of income and summarises the evidence about the top of the income distribution that can be derived from the income tax data. The main results relate to the UK, but comparisons are made with similar evidence for Canada, France, the Netherlands, and the US. The third part of the paper considers the explanation of the observed changes in the distribution and the impact of progressive income taxation. How far are changes in income shares a reflection of the re-arrangement of income? How far are they associated with changes in the composition of top incomes? Conclusions about distributional incidence have to be based on modelling the determination of the personal income distribution, but such modelling is not typically treated in public finance textbooks. The fourth section of the paper considers how the analysis of distributional incidence can be developed, paying specific attention to the explanation of the upper tail of the distribution.